Inregration and Interelation of Bigdata With Cloud Computing: A Review - Saha, T; Das, K (International Journal of Computer Sciences and Engineering, 2025)
In this current era, Information technology opens the door through which human enters into the smart , developing society with modern services in all aspects of living as well as several areas of business, medical and scientific studies, engineering and resulting a massive and exponential growth of data. Handling this voluminous data with traditional information technology frame work becomes a challenging and time demanding task in terms of data collection, storage, retrieval, analysis and application. At the same time cloud computing becomes a powerful model for data processing, storing massive amount of data and perform complex computation. We need to influence cloud computing techniques and solutions to deal with big data problems. In this review paper we focus on integration of big data in cloud environment, a comprehensive description of big data and its features, cloud computing and its characteristics and the relationship between both technologies and challenges it’s facing.